Efeitos da Campomanesia xanthocarpa em parâmetros bioquímicos, hematológicos e de estresse oxidativo em pacientes hipercolestrolêmicos - Klafke, Jonatas Zeni (2009)
In Southern Brazil, the plant Campomanesia xanthocarpa Berg. (Myrtaceae), popularly known as guavirova , has been empirically used for its potential effect in reducing blood cholesterol levels. Since there are no scientific data confirming its popular use, the aim of the present study was to investigate the effect of C. xanthocarpa on biochemical, hematological, anthropometrical and oxidative stress parameters in hypercholesterolemic patients. Thirty three patients were selected according to total cholesterol (TC) levels: 200-240 mg/dL, undesirable level (UL), and >240 mg/dL, hypercholesterolemic level (HL). UL or HL patients were randomly divided into control group (CG), which received placebo capsules, and experimental group 250 (EG 250) or 500 (EG 500), which received either 250 or 500 mg of encapsulated C. xanthocarpa. All groups received a cholesterol restriction diet and capsules once a day. The biochemical (TC, triglycerides, HDL, LDL and VLDL), hematological (hematocrit and hemoglobin), anthropometrical (weight and abdominal circumference) and oxidative stress (protein carbonyl) parameters were measured before, 45 and 90 days after the treatment started. There was no alteration on biochemical, hematological, anthropometric or oxidative stress parameters in UL patients of all groups. However, a significant decrease in TC and LDL levels was observed in HL patients from EG 500 group (reduction of 28±3 and 45±4% to levels before treatment) in relation to CG group patients (reduction of 12±2 and 29±4%). Moreover, a significant reduction in oxidative stress was observed in HL patients of EG 250 (51±12%) and EG 500 groups (34±18%) when compared to levels before treatment. A positive correlation between plasma oxidative stress PC and TC levels was observed. Finally, was demonstrated that C. xanthocarpa extract possesses anti-oxidant properties and 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitory activity in vitro. Confirming its popular use, the treatment with C. xanthocarpa encapsulated reduced blood TC and LDL levels in hypercholesterolemic patients. Besides its effect on cholesterol levels, this plant reduced the oxidative stress in plasma of hypercholesterolemic patients as well.